Thermal power generation during heat cycle near room temperature. (8th December 2017) - Shibata, Takayuki; Fukuzumi, Yuya; Kobayashi, Wataru; Moritomo, Yutaka
Abstract: We demonstrate that a sodium-ion secondary battery (SIB)-type thermocell consisting of two types of Prussian blue analogue (PBA) with different electrochemical thermoelectric coefficients ( S EC ≡ ∂ V /∂ T ; V and T are the redox potential and temperature, respectively) produces electrical energy during heat cycles. The device produces an electrical energy of 2.3 meV/PBA per heat cycle between 295 K (= T L ) and 323 K (= T H ). The ideal thermal efficiency (η = 1.0%), which is evaluated using the heat capacity ( C = 4.16 meV/K) of ideal Na2 Co[Fe(CN)6 ], reaches 11% of the Carnot efficiency (ηth = 8.7%). Our SIB-type thermocell is a promising thermoelectric device that harvests waste heat near room temperature.